Formation of Religious and Honest Character through Halaqah Preaching - Taufik Pelu; Muliaty Amin; Suf Kasman (Jurnal Mercusuar, 2022)
Islamic boarding schools (pondok pesantren) have been able to contribute to shaping the character identity of the next generation of the nation. Religion-based education is capable of building the character of students to become religious and honest individuals. This research aims to understand the process of halaqah preaching in shaping the religious and honest character of students (santri) at Pondok Pesantren Imam Asy Syathiby in Gowa. This field research employs a qualitative method with a focus on preaching and communication. Primary data was obtained through interviews, observations, and documentation. Meanwhile, secondary data was gathered from various literature and sources related to this research. The organization of halaqah preaching begins by dividing the students into several groups. Each group is led by a murobbi (spiritual guide). The students and murobbi determine the schedule of their halaqah preaching sessions, which take place during dawn, afternoon, and night. The content delivered during halaqah preaching includes etiquette teachings from the book "Kitabul Jami’" using various methods such as lectures, storytelling, and direct emulation. The halaqah preaching activities successfully cultivate religious and honest character in the students through the transfer of knowledge and direct emulation facilitated by the murobbi.